PSF and MTF from a bar pattern in digital mammography - Lozano, F R; Rojo, Daniel; Martínez, L C; Ramon, Carlos (Biomedical physics & engineering express, 2024)
Background. The MTF has difficulties being determined (according to the provisions of the IEC standards) in the hospital setting due to the lack of resources. Purpose. The objective of this work is to propose a quantitative method for obtaining the point spread function ( PSF ) and the modulation transfer function ( MTF ) of a digital mammography system from an image of a bar pattern. Methods. The method is based on the measurement of the contrast transfer function ( CTF ) of the system over the image of the bar pattern. In addition, a theoretical model for the PSF is proposed, from which the theoretical CTF of the system is obtained by means of convolution with a square wave (mathematical simulation of the bar pattern). Through an iterative process, the free parameters of the PSF model are varied until the experimental CTF coincides with the one calculated by convolution. Once the PSF of the system is obtained, we calculate the MTF by means of its Fourier transform. The MTF calculated from the model PSF have been compared with those calculated from an image of a 65 μ m diameter gold wire using an oversampling process. Results. The CTF has been calculated for three digital mammographic systems (DMS 1, DMS 2 and DMS 3), no differences of more than 5 % were found with the CTF obtained with the PSF model. The comparison of the MTF shows us the goodness of the PSF model. Conclusions. The proposed method for obtaining PSF and MTF is a simple and accessible method, which does not require a complex configuration or the use of phantoms that are difficult to access in the hospital world. In addition, it can be used to calculate other magnitudes of interest such as the normalized noise power spectrum ( NNPS ) and the detection quantum efficiency ( DQE ).